Real-world validation of a length prediction formula for bedside PICC placement: A single-center retrospective observational study - Jung Won Kwak; Sung-Joon Park; Hwan Hoon Chung (PLoS ONE, 2026)
This study aimed to validate a landmark-based catheter length prediction formula for bedside peripherally inserted central catheter (PICC) placement in a real-world clinical setting, especially in complex environments where advanced navigation technologies may be limited or unsuitable. We retrospectively analyzed 449 consecutive bedside PICC placements performed between March 2022 and September 2025. Catheter insertion length was estimated beforehand using a formula based on anteroposterior chest radiograph (CXR) measurements, including clavicle length and vertebral body units. Final tip positions were assessed by two independent radiologists using post-procedural CXR in relation to the cavoatrial junction (CAJ), with optimal positioning defined as the tip being within ±2.8 cm of the CAJ. Of the 449 cases, technical success was achieved in 436 (97.1%), and optimal tip positioning was seen in 74.3% of successful cases. The interobserver agreement for tip assessment was 98.45% (95% confidence interval: 96.84–99.25%). The average distance from the catheter tip to the CAJ was −0.10 ± 2.59 cm, with a median of 0.0 cm. Rates of optimal positioning did not significantly differ based on operator experience (p = 0.496) or approach side (p = 0.590). Importantly, the technical success rate remained high (97.5%) even in patients with other intravascular devices, such as extracorporeal membrane oxygenation (ECMO) cannulas or hemodialysis catheters. In conclusion, the landmark-based formula offers high predictive accuracy and excellent reproducibility for bedside PICC placement. It serves as a reliable initial safety measure and a practical alternative in complex intensive care settings where real-time navigation is limited or systemically constrained.